2006
DOI: 10.1183/09031936.06.00037906
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that mesothelial cells regulate the acute inflammatory response in talc pleurodesis

Abstract: Intrapleural instillation of talc is used to produce pleurodesis in cases of recurrent malignant pleural effusions. The mechanisms by which pleurodesis is produced remain unknown but may involve either injury or activation of the mesothelium. The aim of the current study was to assess the inflammatory response of pleural mesothelial cells to talc in an experimental model in rabbits.A group of 10 rabbits were injected intrapleurally with talc (200 mg?kg -1 ) and undiluted pleural fluid was collected after 6, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
3
29
0
1
Order By: Relevance
“…When these agents are compared, talc not only causes a greater degree of apoptosis of lung cancer cells than bleomycin at equivalent concentrations, but it also demonstrates selectivity of action by sparing the normal mesothelium, which is not observed with bleomycin or doxycyline. Our in vitro observation was further supported by the discovery of a preserved layer of mesothelial cells despite an intense inflammatory pleural reaction in rabbits treated with talc [8].…”
Section: To the Editorssupporting
confidence: 67%
See 2 more Smart Citations
“…When these agents are compared, talc not only causes a greater degree of apoptosis of lung cancer cells than bleomycin at equivalent concentrations, but it also demonstrates selectivity of action by sparing the normal mesothelium, which is not observed with bleomycin or doxycyline. Our in vitro observation was further supported by the discovery of a preserved layer of mesothelial cells despite an intense inflammatory pleural reaction in rabbits treated with talc [8].…”
Section: To the Editorssupporting
confidence: 67%
“…ANTONY et al [9] demonstrated that patients with extensive pleural carcinomatosis and minimal intervening normal mesothelium had significantly lower quantities of basic fibroblast growth factor in their pleural fluid, compared to those with limited disease who subsequently developed successful pleural symphysis. These findings suggested that a mesothelium free of tumour was necessary for successful pleurodesis [8]. A recent study also showed that an intact pleural mesothelium is critical in modulating the metastatic potential of cancer cells within the pleural space.…”
Section: To the Editorsmentioning
confidence: 91%
See 1 more Smart Citation
“…43 However, we observed higher pleural VEGF levels after the administration of small talc (< 5 µm) compared with mixed talc (90% of particles > 10 µm), whereas TGF-β levels were higher in animals injected with mixed talc, suggesting a possible overlapping of distinct inflammatory mechanisms. 30,44 In addition to inflammatory mediators, an acute serum increase of leukocytes and neutrophils is also observed in both talc groups, coinciding with the acute pleural inflammatory response. However, no conclusion can be drawn about whether the systemic cellular response is the result of the flow of cells from the pleural cavity to the blood circulation or whether it is a direct response to the presence of talc particles in the organs.…”
Section: Systemic Inflammatory Responsementioning
confidence: 87%
“…This is true when mechanical pleural abrasion or pleurectomy is performed, but there is increasing evidence for the new concept that the pleural mesothelium is the primary initiator of the biological mechanisms leading to pleurodesis [17,18]. We already know that the production/release of inflammatory and fibrosis markers by mesothelial cells are essential to achieve a good pleural symphysis, provided that mechanical conditions, as explained above, have been accomplished.…”
Section: Mechanisms Involved In Pleurodesismentioning
confidence: 99%